Sex differences in high opioid dose escalation among Malaysian patients with long term opioid therapy - Zin, Che Suraya; Alias, Nor Elina; Mohd Taufek, Nor Hidayah; Meor Ahmad, Mazlila (Dove Press Ltd., 2019)
Purpose: This study evaluated the risk of opioid dose escalation as it relates to sex differences among patients receiving opioids for long-term therapy.